Kajian Literatur mengenai Arah Pengembangan Ekonomi Kreatif di Indonesia Menuju Tahun 2030 - Rahmat Prayoga; Julius Christian Sitohang Julius Christian Sitohang (LPPM Swadaya Institute of Business and Communication, 2023)
An in-depth look at the potential and challenges of the creative economy in 2030 and the strategies that need to be adopted to achieve a strong, creative, inclusive, and sustainable economic recovery, is presented by researchers compiled in the work of the book